Le numérique vecteur d'un rapport instrumental aux savoirs ? - Anca Boboc; Jean-Luc Metzger (Centre National d'Enseignement à Distance, 2019)
The "digitalization" of companies is accompanied by a system of injunctions for employees: remaining employable, showing autonomy and creativity, while being responsible. In this context, in-company training is a key issue. But what can be its real contribution, when it is itself the object of technico-pedagogical experiments and when the function of trainer is questioned? In order to answer that, we present the results of a research carried out on a digital training, fully remote and without any trainer. Intended for the internal actors of training, it aims to familiarize them with the educational uses of digital trainings and devices. To explain the very high dropout rate that characterizes it, we analyzed the type of interest leading to training and the social character of the knowledge appropriation. Thus, we show, on the one hand, that the implementation of this type of digital training, leads learners to adopt an instrumental relation to training and, on the other hand, it introduces a new source of inequality between them. To this form of industrialization, that we call radical, we suggest to oppose a reflexive industrialization where digitalization would foster reflexive approaches through which trainers reflect on the reorganization of their practices.